The Lhx1-Ldb1 complex interacts with Furry to regulate microRNA expression during pronephric kidney development - Espiritu, Eugenel B. (2018)
The molecular events driving specification of the kidney have been well characterized. However, how the initial kidney field size is established, patterned, and proportioned is not well characterized. Lhx1 is a transcription factor expressed in pronephric progenitors and is required for specification of the kidney, but few Lhx1 interacting proteins or downstream targets have been identified. By tandem-affinity purification, we isolated FRY like transcriptional coactivator (Fryl), one of two paralogous genes, fryl and furry (fry), have been described in vertebrates. Both proteins were found to interact with the Ldb1-Lhx1 complex, but our studies focused on Lhx1/Fry functional roles, as they are expressed in overlapping domains. We found that Xenopus embryos depleted of fry exhibit loss of pronephric mesoderm, phenocopying the Lhx1-depleted animals. In addition, we demonstrated a synergism between Fry and Lhx1, identified candidate microRNAs regulated by the pair, and confirmed these microRNA clusters influence specification of the kidney. Therefore, our data shows that a constitutively-active Ldb1-Lhx1 complex interacts with a broadly expressed microRNA repressor, Fry, to establish the kidney field.